Construction of microenvironment onto titanium substrates to regulate the osteoblastic differentiation of bone marrow stromal cells in vitro and osteogenesis in vivo1. Issue 3 (28th August 2012) - Lai, Min; Cai, Kaiyong; Hu, Yan; Zhang, Yuan; Li, Liqi; Luo, Zhong; Hou, Yanhua; Li, Jinghua; Ding, Xingwei; Chen, Xiuyong
Abstract: To mimic the extracellular matrix of natural bone, apatite/gelatin composite was deposited onto nanostructured titanium substrates via a coprecipitation method, which was pretreated by potassium hydroxide and heat treatment to generate an anticorrosive nanostructured layer. The successful formation of the apatite/gelatin nanocomposite onto titanium surfaces was revealed by Fourier transform infrared spectroscopy, field‐emission scanning electron microscopy, atomic force microscopy (AFM), and thin film X‐ray diffraction (TF‐XRD) measurements, respectively. The immunofluorescence staining of vinculin revealed that the apatite/gelatin nanocomposite deposited titanium substrate was favorable for cell adhesion. More importantly, bone marrow stromal cells cultured onto the apatite/gelatin nanocomposite deposited titanium substrates displayed significantly higher ( p < 0.05 or p < 0.01) proliferation and differentiation levels of alkaline phosphatase, mRNA expressions of osteocalcin (OC), osteopontin (OPN), and collagen type I (Col I), and OC content after culture for 7, 14, and 21 days, respectively, which was also revealed by the immunofluorescence analysis of OC and OPN expression. The deposition of apatite/gelatin nanocomposite improved bone density ( p < 0.05) and bone‐implant contact rate ( p < 0.05), which was reflected by microcomputed tomography analysis and histological evaluation in vivo using a rabbit model. This work provides an approach to fabricate high‐performance titanium‐based implants with enhanced bone osseointegration. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 653–666, 2013.